Cover Image, Volume 9, Issue 6. (12th October 2017) - Burrowes, Kelly S.; De Backer, Jan; Kumar, Haribalan
Abstract : The cover image, by Kelly S. Burrowes et al., is based on Advanced Review Image‐based computational fluid dynamics in the lung: virtual reality or new clinical practice?, DOI: 10.1002/wsbm.1392 . Abstract : The cover image, by Kelly S. Burrowes et al., is based on Advanced Review Image‐based computational fluid dynamics in the lung: virtual reality or new clinical practice?, DOI: 10.1002/wsbm.1392 .